Validity and reliability of the Turkish version of the Self-Care of Coronary Heart Disease Inventory - BAYRAK, BETÜL; OĞUZ, SIDIKA (WILEY, 2021)
Aim This study aimed to adapt a culturally suitable and functional Turkish version of the Self-Care of Coronary Heart Disease Inventory to evaluate its reliability and validity to measure Turkish coronary heart disease patients' levels of self-care. Methods The study was performed at the cardiology clinics of three hospitals in Istanbul, Turkey. Content validity index, exploratory and confirmatory factor analysis were used in the validity analyses. In the reliability analyses, pearson's correlation coefficient, cronbach's alpha scores and test-retest reliability were used. The validity and reliability analyses were conducted with 222 coronary heart disease patients, whereas the test-retest analysis was carried out with 50 patients. Results The three subscale and 22-item Turkish Inventory's factorial structure was similar to the English version. The results of the confirmatory factor analysis showed a good model fit. Cronbach's alpha ranged from .63 to .95, and no statistically significant differences were found in the test-retest reliability analysis (P > .05). Conclusion Turkish version of the Self-Care of Coronary Heart Disease Inventory is a valid and reliable tool for determination of coronary heart disease patients' self-care in Turkey.
Keywords: coronary heart disease; instrument; nursing; self-care